Multiomics analysis investigating the impact of a high-fat diet in female Sprague–Dawley rats: alterations in plasma, intestinal metabolism, and microbial composition - Zhang, Jiacheng; Hu, Binhong; Deng, Xin; Sun, Rong; Zhang, Rong; Chen, Kuo; Guo, Wenzhi (Frontiers in Nutrition, 2024)
With improvements in living conditions, modern individuals exhibit a pronounced inclination towards a high-fat diet, largely because of its distinctive gustatory appeal. However, the association between high-fat diets and metabolic complications has largely been ignored, and metabolic diseases such as obesity and non-alcoholic fatty liver disease now constitute a major public health concern. Because high-fat diets increase the risk of metabolic diseases, a thorough investigation into the impact of highfat diets on gut microbiota and metabolism is required. In the present study, we utilize 16S rRNA sequencing and untargeted metabolomics analysis to demonstrate that SD rats fed a high-fat diet exhibited marked alterations in gut microbiota. These include a decreased abundance at phylum level for Verrucomicrobiota, and a decreased abundance at genus level for Akkermansia, Ralstonia, Bacteroides, and Faecalibacterium. Additionally, significant changes were observed in both intestinal and plasma metabolite levels, including an upregulation of bile acid metabolism, an upregulation of glucose-lipid metabolism, and increased levels of metabolites such as norlithocholic acid, cholic acid, D-fructose, D-mannose, fructose lactate, and glycerophosphocholine. We also investigated the correlations between microbial communities and metabolites, revealing a significant negative